2012
DOI: 10.1002/ejsp.1845
|View full text |Cite
|
Sign up to set email alerts
|

Breaking apart the typical mortality salience manipulation: Two questions, two outcomes

Abstract: The typical mortality salience manipulation asks participants to reflect on two questions, one about the emotions associated with the thought of death and the other about what happens after one dies. In five experiments, we separated these two questions and gave participants either one or a control question. In Experiment 1, participants' responses to the afterlife question were coded as being informed more by cultural knowledge and values compared with responses to the emotion question. Experiments 2 and 3 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Previous research has found that small differences in the wording of the MS manipulation can elicit different effects on the samples (Cozzolino, Staples, Meyers, & Sambocet, ). Burgin, Sanders, vanDellen, & Martin () have suggested that MS manipulations using the “afterlife” referent may result in greater worldview defence than MS manipulations using the “emotional feeling” referent. Although we used the “emotional” MS manipulation which may have had a smaller effect on worldview defence, it did significantly increase support for divine power and policies that combat violent extremism.…”
Section: Studymentioning
confidence: 99%
“…Previous research has found that small differences in the wording of the MS manipulation can elicit different effects on the samples (Cozzolino, Staples, Meyers, & Sambocet, ). Burgin, Sanders, vanDellen, & Martin () have suggested that MS manipulations using the “afterlife” referent may result in greater worldview defence than MS manipulations using the “emotional feeling” referent. Although we used the “emotional” MS manipulation which may have had a smaller effect on worldview defence, it did significantly increase support for divine power and policies that combat violent extremism.…”
Section: Studymentioning
confidence: 99%
“…In many studies of MS, members of the experimental group are asked to write about their own death, while those in the control group are instructed to write about an event unrelated to death (although, in many cases, one with negative connotations). The results obtained from such studies show that much of the behaviour we present and experience on a daily basis is influenced by unconscious thoughts about our own death (Burke et al, 2010;Burgin et al, 2012), reinforcing the defence of ideals or values related to distal defences.…”
Section: Introductionmentioning
confidence: 97%
“…Distal defences, on the other hand, prevent the thoughts of death that are still accessible from remaining in the subconscious (Pyszczynski, Solomon & Greenberg, 2015). Two main distal defences have been described: self-esteem and belief in the validity of one's own cultural outlook on the world and its associated values (Burgin, Sanders, Vandellen & Martin, 2012;Burke, Martens & Faucher, 2010; anales de psicología, 2017, vol. 33, nº 3 (october) Routledge, Juhl & Vess, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations